2014
DOI: 10.1155/2014/649034
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Ubiquitous and UniqueLeptospiraStrains from the Collection of Russian Centre for Leptospirosis

Abstract: Background and Aim. Leptospira, the causal agent of leptospirosis, has been isolated from the environment, patients, and wide spectrum of animals in Russia. However, the genetic diversity of Leptospira in natural and anthropurgic foci was not clearly defined. Methods. The recent MLST scheme was used for the analysis of seven pathogenic species. 454 pyrosequencing technology was the base of the whole genome sequencing (WGS). Results. The most wide spread and prevalent Leptospira species in Russia were L. interr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…This sequence type seems to be responsible for up to 90% of human leptospirosis cases in São Paulo, Brazil (Romero, Blanco, & Galloway, 2011) and was also identified in a rat, pig and human hosts in Argentina (Caimi et al, 2012). It seems to be also frequent in Russia (Voronina et al, 2014) and China (Zhang et al, 2015). Most interesting, Previous studies noticed that MLST approaches may contribute to unravel potential associations between specific Leptospira STs and their hosts and geographic regions of origin (Boonsilp et al, 2013;Dietrich et al, 2018Dietrich et al, , 2014.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This sequence type seems to be responsible for up to 90% of human leptospirosis cases in São Paulo, Brazil (Romero, Blanco, & Galloway, 2011) and was also identified in a rat, pig and human hosts in Argentina (Caimi et al, 2012). It seems to be also frequent in Russia (Voronina et al, 2014) and China (Zhang et al, 2015). Most interesting, Previous studies noticed that MLST approaches may contribute to unravel potential associations between specific Leptospira STs and their hosts and geographic regions of origin (Boonsilp et al, 2013;Dietrich et al, 2018Dietrich et al, , 2014.…”
Section: Discussionmentioning
confidence: 90%
“…This sequence type seems to be responsible for up to 90% of human leptospirosis cases in São Paulo, Brazil (Romero, Blanco, & Galloway, ) and was also identified in a rat, pig and human hosts in Argentina (Caimi et al, ). It seems to be also frequent in Russia (Voronina et al, ) and China (Zhang et al, ). Most interesting, ST (7LBoonsilp) 17 isolates were responsible for an outbreak of severe leptospirosis among capuchin monkeys in a Colombian wildlife rehabilitation centre (Szonyi, Agudelo‐Florez, Ramirez, Moreno, & Ko, ).…”
Section: Discussionmentioning
confidence: 99%
“…ST17 was identified in 90 strains of serogroup Icterohaemorrhagiae in Sao Paulo [36]. Five common STs, ST37, ST17, ST 199, ST110, and ST146, were reported to have a longterm and ubiquitous distribution in Russia [37]. ST37, ST118 and ST119 were isolated from dogs in Japan [38].…”
Section: Discussionmentioning
confidence: 99%
“…All the 3 serogroup Icterohaemorrhagiae strains isolated between 1993~2005 were identified as ST17 [ 21 ]. Among 11 serogroup Icterohaemorrhagiae strains in Russia, four STs (ST17, ST199, ST23 and ST206) were found [ 22 ]. It was previously reported that Icterohaemorrhagiae was the most prevalent serogroup in Brazil [ 23 , 33 ], and all the 90 serogroup Icterohaemorrhagiae strains isolated between 1986~2009 in the state of Sao Paulo were identified as ST17 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%